ФОРМИРОВАНИЕ ТВОРЧЕСКОГО ПОТЕНЦИАЛА ЛИЧНОСТИ ЧЕРЕЗ ИСПОЛЬЗОВАНИЕ ПРОБЛЕМНО-ПОИСКОВЫХ ЗАДАНИЙ ТВОРЧЕСКОГО ХАРАКТЕРА - Саулембекова, Р.М.; Кабдушева, А.Ж. (My University, 2019)
Аннотация В данной статье рассматривается научно-теоретические основы проблемно-поисковой технологии обучения. Содержание проблемного обучения, типы задач, используемых на уро- ках биологии, помогающие формировать предметную компетентность. Abstract This article discusses the scientific and theoretical foundations of problem-retrieval learning technologies. The content of problem-based learning, the types of assignments used in biology lessons, help to form the subject competence.
Formation of creative potential of personality through the use of problem-search tasks of creative character
Keywords: проблемно-поисковая технология обучения; проблемное обучение; проблемные ситуации; траектория развития личности; problem-search technology training; problem learning; problem situations; the trajectory of personal development